Manufacturing method of photosensitive microcrystalline glass

Through mask exposure and crystallization heat treatment technology, photosensitive microcrystalline glass containing blackened and transparent parts was prepared, solving the problem of insufficient pattern accuracy and mechanical properties of existing photosensitive microcrystalline glasses, and achieving high-precision and high-performance photosensitive microcrystalline glass manufacturing.

CN119797760APending Publication Date: 2025-04-11CDGM GLASS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022082.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-22
Filing Date
2024-06-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing photosensitive microcrystalline glass has poor pattern accuracy and its mechanical properties are difficult to meet the needs of high-performance electronic equipment.

Method used

By forming a photosensitive glass and using mask exposure treatment and crystallization heat treatment, a photosensitive microcrystalline glass containing a blackened part and a transparent part is prepared. The blackened part contains a crystal phase and the transparent part does not contain a crystal phase.

Benefits of technology

The photosensitive microcrystalline glass with high pattern accuracy has excellent mechanical properties and can meet the requirements of high-performance electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231670690000151
    Figure BDA0005231670690000151
  • Figure BDA0005231670690000201
    Figure BDA0005231670690000201
  • Figure BDA0005231670690000211
    Figure BDA0005231670690000211
Patent Text Reader

Abstract

The invention provides a manufacturing method of photosensitive microcrystalline glass with relatively high pattern precision. The manufacturing method of the photosensitive microcrystalline glass comprises the following steps that photosensitive glass is formed, the photosensitive glass is formed into the photosensitive microcrystalline glass through a crystallization process, the photosensitive microcrystalline glass comprises one or more blackened parts and one or more transparent parts, the blackened parts contain crystalline phases, and the transparent parts do not contain crystalline phases. The pattern precision of the photosensitive microcrystalline glass manufactured by the manufacturing method of the photosensitive microcrystalline glass is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application for the invention patent application with application number 202410784178.3, application date June 18, 2024, and name “Photosensitive Glass and Photosensitive Microcrystalline Glass”. Technical Field

[0002] The invention relates to a method for manufacturing photosensitive microcrystalline glass, and in particular to a method for manufacturing photosensitive microcrystalline glass with high pattern accuracy. Background Art

[0003] In recent years, glass materials are commonly used in various displays and display devices of many electronic products, such as mobile phones, music players, e-book readers, notepads, tablets, laptops, ATMs and other similar devices. The protective materials used to form the shells of display devices and electronic devices are usually selected to meet the mechanical requirements related to the end use of the electronic devices. With the diversification of market demand, the use scenarios of protective glass materials are becoming more and more complex, and the role they play is no longer just as the protection of internal electronic devices, and sometimes they also need to have other functions. For example, in the vital signs monitoring of smart watches, the glass material needs to be partially transparent, but it needs to be shielded in other places to avoid the interference of stray light. Therefore, the glass material needs to have both black and transparent parts, which poses new challenges to the glass manufacturing process technology. In the prior art, the above-mentioned cover material can be manufactured by embedded design using two different materials, transparent and black, but due to the different strengths of the two materials, the large difference in expansion coefficients, and the need to process through holes, there are microcracks on the inner wall of the glass, resulting in reduced strength of the cover material, and difficult processing for smaller holes or special-shaped graphics, and high production costs. The linear expansion coefficient of the photosensitive glass in the prior art is relatively high, and the pattern precision formed by the photosensitive microcrystalline glass produced therefrom is relatively poor; meanwhile, its mechanical properties are also difficult to meet the requirements of use in high-performance electronic equipment and the like. Summary of the invention

[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a method for manufacturing photosensitive microcrystalline glass with high pattern accuracy.

[0005] The solution adopted by the present invention to solve the technical problem is:

[0006] (1) A method for manufacturing photosensitive microcrystalline glass, the method comprising the following steps: forming photosensitive glass, subjecting the photosensitive glass to a crystallization process to form photosensitive microcrystalline glass, wherein the photosensitive microcrystalline glass comprises one or more blackened portions and one or more transparent portions, wherein the blackened portions contain a crystalline phase, and the transparent portions do not contain a crystalline phase.

[0007] (2) According to the method for manufacturing photosensitive microcrystalline glass described in (1), the crystallization process includes performing mask exposure treatment on the photosensitive glass and then performing crystallization heat treatment, the mask exposure treatment includes ultraviolet exposure to a specific position or area of ​​the photosensitive glass, the wavelength of the ultraviolet light is preferably 280 to 360 nm, more preferably 300 to 330 nm, and further preferably 313 nm, and the exposure time is preferably 5 to 60 minutes.

[0008] (3) According to the method for manufacturing photosensitive microcrystalline glass described in (1) or (2), the crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes a nucleation process at a first temperature and then a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

[0009] (4) According to the method for manufacturing a photosensitive glass-ceramic according to any one of (1) to (3), the photosensitive glass-ceramic contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase, more preferably, in the blackened portion of the photosensitive glass-ceramic, the weight percentage of the lithium metasilicate crystalline phase is 5 to 50%, further preferably, in the blackened portion of the photosensitive glass-ceramic, the weight percentage of the lithium metasilicate crystalline phase is 5 to 40%, and further preferably, in the blackened portion of the photosensitive glass-ceramic, the weight percentage of the lithium metasilicate crystalline phase is 10 to 30%.

[0010] (5) According to the method for manufacturing a photosensitive microcrystalline glass according to any one of (1) to (4), the average transmittance T of the transparent part of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm in the wavelength range of 400 to 800 nm is 400-800nm is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2-1.5 mm in the wavelength range of 400-800 nm is 400-800nm 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm at 870 nm 870nm is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm at 940 nm 940nmIt is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.

[0011] (6) According to the method for manufacturing a photosensitive microcrystalline glass according to any one of (1) to (5), the components of the photosensitive microcrystalline glass, expressed in weight percentage, contain: SiO2: 65-78%, preferably SiO2: 68-77%, more preferably SiO2: 69.5-75.5%; and / or R2O+Li2O+Al2O3: 15-30%, preferably R2O+Li2O+Al2O3: 17.5-29.5%, more preferably R2O+Li2O+Al2O3: 18.5-26%, further preferably R2O+Li2O+Al2O3: 20-25%; and / or ZrO2: 1.5-10%, preferably ZrO2: 2-8%, more preferably ZrO2: 3-6.5%; and / or CeO2: 0.01-0.6%, preferably CeO2: 0.07-0.4%, more preferably CeO2: 0. 08~0.3%; and / or Ag2O: 0.01~0.8%, preferably Ag2O: 0.1~0.6%, more preferably Ag2O: 0.2~0.5%; and / or Sb2O3+SnO2: 0.05~1.2%, preferably Sb2O3+SnO2: 0.1~1%, more preferably Sb2O3+SnO2: 0.2~0.7%; and / or Ln2O3: 0~5%, preferably Ln2O 3: 0-3%, more preferably Ln2O3: 0-1%, further preferably no Ln2O3; and / or Fe2O3: 0-1%, preferably Fe2O3: 0-0.5%, more preferably Fe2O3: 0-0.2%, further preferably no Fe2O3, said R2O is one or two of Na2O, K2O, and Ln2O3 is one or more of La2O3, Gd2O3, Y2O3.

[0012] (7) The method for manufacturing a photosensitive glass-ceramic according to any one of (1) to (6), wherein the components of the photosensitive glass-ceramic are expressed in weight percentage, wherein: SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, and more preferably SiO2 / Li2O is 7.0 to 8.5; and / or (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; and / or Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0; and / or Or (SiO2+Li2O) / ZrO2 is 8.0~55.0, preferably (SiO2+Li2O) / ZrO2 is 10.0~37.0, more preferably (SiO2+Li2O) / ZrO2 is 12.0~25.0, and further preferably (SiO2+Li2O) / ZrO2 is 13.0~20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0~7.5, preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7~6.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3~6.0, and further preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8~5.8.

[0013] (8) According to the method for manufacturing photosensitive microcrystalline glass according to any one of (1) to (7), the components of the photosensitive microcrystalline glass are expressed in weight percentage, wherein: (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; and / or Ag2O / CeO2 is 1.0 to 10.0, preferably Ag2O / CeO2 is 1.5 to 6.5, more preferably Ag2O / CeO2 is 2.0 to 4.5; and / or ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, further preferably ZrO2 / (Ag2O+CeO2) is 1.5 to 6.5, more preferably Ag2O / CeO2 is 2.0 to 4.5; and / or ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, further preferably ZrO2 / (Ag 2O+CeO2) is 11.0 to 18.0; and / or (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 20.0, more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0 to 12.5, and further preferably (Ag2O+SnO2+Sb2O3) / CeO 2 is 7.5~10.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1~10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4~5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7~3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5~3.2.

[0014] (9) According to the method for manufacturing photosensitive microcrystalline glass according to any one of (1) to (8), the components of the photosensitive microcrystalline glass are expressed in weight percentage, wherein: R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; and / or Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; and / or Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; and / or Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%, wherein R2O is one or both of Na2O and K2O.

[0015] (10) According to the method for manufacturing a photosensitive microcrystalline glass as described in any one of (1) to (9), the refractive index n of the transparent part of the photosensitive microcrystalline glass is dis 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284; and / or Young's modulus E is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 ; and / or the ball drop test height I is 200 mm or more, preferably 300 mm or more, more preferably 400 mm or more; and / or the dielectric loss tanδ is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 ; and / or dielectric constant ε r 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0; and / or linear expansion coefficient α 20℃-300℃ 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0016] (11) Photosensitive microcrystalline glass, made by any of the photosensitive microcrystalline glass manufacturing methods described in (1) to (10).

[0017] (12) A photosensitive microcrystalline glass product, which is manufactured by the method for manufacturing photosensitive microcrystalline glass described in any one of (1) to (10).

[0018] (13) According to the photosensitive microcrystalline glass product described in (12), the chemical strengthening process includes immersing the photosensitive microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.

[0019] (14) According to the photosensitive microcrystalline glass product described in (12) or (13), the drop ball test height II of the photosensitive microcrystalline glass product is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.

[0020] (15) A glass cover plate comprising the photosensitive microcrystalline glass described in (11), or a photosensitive microcrystalline glass product described in any one of (12) to (14).

[0021] (16) A glass component comprising the photosensitive glass-ceramic described in (11), or a photosensitive glass-ceramic product described in any one of (12) to (14).

[0022] (17) A device comprising the photosensitive microcrystalline glass described in (11), and / or the photosensitive microcrystalline glass product described in any one of (12) to (14), and / or the glass cover plate described in (15), and / or the glass component described in (16).

[0023] The beneficial effect of the present invention is that the pattern precision of the photosensitive glass-ceramic manufactured by the manufacturing method of the photosensitive glass-ceramic of the present invention is high. In some embodiments, the photosensitive glass-ceramic and the photosensitive glass-ceramic products of the present invention have excellent mechanical properties. DETAILED DESCRIPTION

[0024] Below, the embodiments of the present invention are described in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, about the repeated description part, although there is a situation of appropriate omission of description, the main purpose of the invention will not be limited thereby.

[0025] The photosensitive glass-ceramics and photosensitive glass-ceramics products of the present invention are materials having a crystalline phase (sometimes also referred to as a crystal) and a glass phase, which are different from amorphous solids. The crystalline phase of the photosensitive glass-ceramics and photosensitive glass-ceramics products can be identified by the peak angle appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.

[0026] After repeated experiments and studies, the inventors of the present invention obtained the photosensitive microcrystalline glass or photosensitive microcrystalline glass products of the present invention by regulating the content and content ratio of the specific components constituting the photosensitive microcrystalline glass and photosensitive microcrystalline glass products to specific values ​​and precipitating a specific crystalline phase.

[0027] In some embodiments, the photosensitive glass-ceramics of the present invention comprises one or more blackened portions and one or more transparent portions, wherein the transparent portions refer to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the photosensitive microcrystalline glass in the 400-800nm ​​band when the photosensitive microcrystalline glass is processed into a thickness of 0.2-1.5mm. 400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the photosensitive glass-ceramics contains a crystalline phase, and the transparent portion of the photosensitive glass-ceramics does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the photosensitive glass-ceramics is uniformly distributed.

[0028] In some embodiments, the photosensitive glass-ceramic product of the present invention comprises one or more blackened parts and one or more transparent parts, wherein the transparent part refers to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the photosensitive microcrystalline glass product in the 400-800nm ​​band when the photosensitive microcrystalline glass product is processed into a thickness of 0.2-1.5mm. 400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the photosensitive glass-ceramic article contains a crystalline phase, and the transparent portion of the photosensitive glass-ceramic article does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the photosensitive glass-ceramic article is uniformly distributed.

[0029] In some embodiments, the photosensitive glass-ceramics or photosensitive glass-ceramics products of the present invention are entirely blackened parts, and the blackened parts refer to the average transmittance (T 400-800nm ) is less than 5.0%. In some embodiments, the crystalline phase of the blackened portion of the photosensitive glass-ceramic or the photosensitive glass-ceramic article is uniformly distributed.

[0030] In some embodiments, the photosensitive glass-ceramics or photosensitive glass-ceramics products of the present invention are entirely transparent, and the transparent portion refers to the average transmittance (T) of the photosensitive glass-ceramics or photosensitive glass-ceramics products in the 400-800nm ​​band when the photosensitive glass-ceramics or photosensitive glass-ceramics products are processed into a thickness of 0.2-1.5mm. 400-800nm ) is more than 85.0%.

[0031] In some embodiments, the blackened portion in the photosensitive glass-ceramics or photosensitive glass-ceramics product of the present invention can form a pattern of any shape and / or size.

[0032] The following is an explanation of the scope of each component (ingredient) of the photosensitive glass, photosensitive glass-ceramic and photosensitive glass-ceramic products of the present invention. In this specification, unless otherwise specified, the content of each component is expressed in weight percentage (wt%) relative to the total amount of the photosensitive glass, photosensitive glass-ceramic or photosensitive glass-ceramic product material converted into an oxide composition. Here, the "composition converted into oxides" refers to the case where the oxides, composite salts and hydroxides used as raw materials for the photosensitive glass, photosensitive glass-ceramic or photosensitive glass-ceramic product of the present invention decompose and transform into oxides when melted, and the total amount of the oxide material is taken as 100%. In addition, in this specification, when it is only referred to as glass, it is the photosensitive glass before crystallization (i.e., crystallization process treatment), the photosensitive glass after crystallization (i.e., crystallization process treatment) is called photosensitive glass-ceramic, and the photosensitive glass-ceramic product refers to the product obtained after the photosensitive glass-ceramic is chemically strengthened.

[0033] Unless otherwise indicated in specific cases, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoints, as well as all integers and fractions within the range, without limitation to the specific values ​​listed when the range is defined. The term "about" as used herein means that the formula, parameters and other quantities and features are not and need not be exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors and measurement errors, etc. "And / or" as used herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0034] In some embodiments of the present invention, the crystalline phase (crystal) in the photosensitive glass-ceramic or photosensitive glass-ceramic product contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase (Li2SiO3) crystalline phase. In some embodiments, the lithium metasilicate crystalline phase has a higher weight percentage than other crystalline phases. In some embodiments, the crystalline phase in the photosensitive glass-ceramic or photosensitive glass-ceramic product includes only a lithium metasilicate crystalline phase.

[0035] In some embodiments, in the blackened portion of the photosensitive glass-ceramics or photosensitive glass-ceramics products, the weight percentage of the lithium metasilicate crystalline phase is 5 to 50%, preferably the weight percentage of the lithium metasilicate crystalline phase is 5 to 40%, and more preferably the weight percentage of the lithium metasilicate crystalline phase is 10 to 30%. In some embodiments, in the blackened portion of the photosensitive glass-ceramics or photosensitive glass-ceramics products, the weight percentage of the lithium metasilicate crystalline phase is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%.

[0036] SiO2 is a glass-forming oxide and a skeleton for forming glass. It has a low dielectric constant and dielectric loss. SiO2 is a component of lithium metasilicate in photosensitive glass-ceramics. When the SiO2 content is less than 65%, the hardness and expansion coefficient of the glass decrease, and the dielectric constant and dielectric loss of the glass increase. When the SiO2 content is higher than 78%, the transmittance of the blackened part of the photosensitive glass-ceramics and photosensitive glass-ceramics products increases. Therefore, the SiO2 content ranges from 65 to 78%, preferably from 68 to 77%, and more preferably from 69.5 to 75.5%. In some embodiments, the SiO2 may include about 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%.

[0037] Li2O is the main component for forming crystals in the photosensitive glass-ceramics and photosensitive glass-ceramics products of the present invention. When the content of Li2O is less than 5%, the crystal content of the photosensitive glass-ceramics or photosensitive glass-ceramics products decreases, and the transmittance of the blackened part is higher; when the content of Li2O is greater than 15%, the Young's modulus and the drop ball test height of the glass decrease, and the refractive index and dielectric loss of the glass increase. At the same time, the part of the photosensitive glass that is not exposed to ultraviolet light during the crystallization process is easy to crystallize during the heat treatment process, and the transmittance of the transparent part of the photosensitive glass-ceramics and photosensitive glass-ceramics products decreases. Therefore, the content of Li2O is limited to 5-15%, preferably 7-13%, and more preferably 8.5-12%. In some embodiments, about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% Li2O may be included.

[0038] The inventors have found that, in some embodiments, the hardness and drop ball test height of the glass increase with the increase of the SiO2 / Li2O value, and the refractive index decreases with the increase of the SiO2 / Li2O value. At the same time, when SiO2 / Li2O is lower than 5.5, the transmittance of the transparent part of the photosensitive glass-ceramics and photosensitive glass-ceramics products decreases, and the transmittance of the blackened part increases; when SiO2 / Li2O exceeds 10.0, the crystal content of the blackened part of the photosensitive glass-ceramics and photosensitive glass-ceramics products is low, and the transmittance of the blackened part increases. Therefore, in some embodiments, preferably SiO2 / Li2O is 5.5 to 10.0, more preferably SiO2 / Li2O is 6.0 to 9.0, and further preferably SiO2 / Li2O is 7.0 to 8.5, the transparent part of the photosensitive glass-ceramics and photosensitive glass-ceramics products has a higher transmittance in the visible light band, and the transmittance of the blackened part is lower, which is particularly suitable for the optical signal channel or light shielding system of electronic products. In some embodiments, the value of SiO2 / Li2O can be 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.

[0039] Alkali metal oxide R2O (R2O is one or both of Na2O and K2O) can promote the precipitation of lithium metasilicate crystals and improve the transmittance of the blackened part of photosensitive glass-ceramics and photosensitive glass-ceramics products. When the R2O content is less than 2%, the crystal content of photosensitive glass-ceramics and photosensitive glass-ceramics products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved; when the R2O content is greater than 12%, the Young's modulus and the drop ball test height of the glass decrease, and the refractive index, dielectric constant and dielectric loss of the glass increase. Therefore, the content of R2O is limited to 2-12%, preferably 3-10%, and more preferably 4-8%. In some embodiments, about 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% R2O may be included.

[0040] Al2O3 can inhibit the decrease in the transmittance of the transparent part of photosensitive microcrystalline glass and photosensitive microcrystalline glass products after mask exposure and heat treatment, and improve the strength and hardness of the glass, and enhance the chemical stability of the glass. When the content of Al2O3 is less than 3%, the hardness and Young's modulus of the glass decrease, and the linear expansion coefficient increases; when the content of Al2O3 is higher than 12%, the dielectric constant and dielectric loss of the glass increase, the crystal content of the blackened part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products decreases, and the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. Therefore, the content of Al2O3 is 3-12%, preferably 4-10%, and more preferably 5-9%. In some embodiments, about 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% Al2O3 may be included.

[0041] In some embodiments, when the total content of R2O, Li2O and Al2O3 R2O+Li2O+Al2O3 is less than 15%, the refractive index, hardness and Young's modulus of the glass are reduced, and when R2O+Li2O+Al2O3 is greater than 30%, the dielectric constant and dielectric loss of the glass are increased. Therefore, preferably R2O+Li2O+Al2O3 is 15-30%, more preferably R2O+Li2O+Al2O3 is 17.5-29.5%, further preferably R2O+Li2O+Al2O3 is 18.5-26%, and further preferably R2O+Li2O+Al2O3 is 20-25%. In some embodiments, R2O+Li2O+Al2O3 is approximately 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, or 30%.

[0042] The inventors have found through a large number of experimental studies that in some embodiments, by controlling the ratio of the total content of SiO2 and Al2O3 SiO2+Al2O3 to the total content of Li2O, Na2O, and K2O Li2O+Na2O+K2O (SiO2+Al2O3) / (Li2O+Na2O+K2O) in the range of 3.0 to 7.5, the transmittance of the blackened part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products is lower, and the refractive index of the glass is lower, which can reduce the reflectivity of the light signal on the glass surface and increase the incidence rate of the light signal. Therefore, the preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, the more preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, the further preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and the further preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8. In some embodiments, the value of (SiO2+Al2O3) / (Li2O+Na2O+KO) may be 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5.

[0043] ZrO2 can adjust the accuracy of the black pattern formed by the blackened part of the glass after mask exposure, improve the interface distinction between the exposed part and the unexposed part, and prevent the unexposed part from crystallizing near the interface after heat treatment, so as to maintain the high transmittance of the unexposed part in the visible light band after heat treatment, and ensure that the blackened part has a lower transmittance after heat treatment of the exposed part. When the ZrO2 content is lower than 1.5%, the expansion coefficient of the glass increases, and the unexposed part is easy to crystallize during heat treatment of the glass, resulting in a decrease in the transmittance of the transparent part. When the ZrO2 content is higher than 10%, the crystal content of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. Therefore, the ZrO2 content is 1.5-10%, preferably 2-8%, and more preferably 3-6.5%. In some embodiments, ZrO2 may be included at about 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.

[0044] In some embodiments, the ratio (K2O+Na2O) / ZrO2 between the total content of K2O and Na2O K2O+Na2O and the content of ZrO2 is controlled within the range of 0.5 to 7.1, the transmittance of the transparent part of the photosensitive microcrystalline glass and the photosensitive microcrystalline glass product is high, the hardness and Young's modulus of the glass are high, and the dielectric constant of the glass is low. Therefore, preferably (K2O+Na2O) / ZrO2 is 0.5 to 7.1, more preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and further preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5. In some embodiments, the value of (KO+NaO) / ZrO may be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 6.0, 6.5, 7.0, 7.1.

[0045] In some embodiments, controlling the ratio of Li2O content to ZrO2 content Li2O / ZrO2 within the range of 1.0 to 7.5 can make the glass have a lower refractive index and dielectric loss, can improve the accuracy of pattern formation in the photosensitive microcrystalline glass and photosensitive microcrystalline glass products after the glass is exposed through a mask and heat treated, and the transparent part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, preferably Li2O / ZrO2 is 1.0 to 7.5, more preferably Li2O / ZrO2 is 1.2 to 5.0, further preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0. In some embodiments, the value of Li2O / ZrO2 may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5.

[0046] In some embodiments, controlling the ratio of the total content of SiO2 and Li2O SiO2 + Li2O to the content of ZrO2 (SiO2 + Li2O) / ZrO2 within the range of 8.0 to 55.0 can improve the hardness of the glass and the drop ball test height, reduce the expansion coefficient and dielectric constant of the glass, improve the accuracy of pattern formation in photosensitive microcrystalline glass and photosensitive microcrystalline glass products after mask exposure and heat treatment, and improve the drop ball test height of photosensitive microcrystalline glass and photosensitive microcrystalline glass products; the transmittance of the blackened portion of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products is low. Therefore, the preferred (SiO2+Li2O) / ZrO2 is 8.0~55.0, the more preferred (SiO2+Li2O) / ZrO2 is 10.0~37.0, the further preferred (SiO2+Li2O) / ZrO2 is 12.0~25.0, and the further preferred (SiO2+Li2O) / ZrO2 is 13.0~20.0. In some embodiments, the value of (SiO2+Li2O) / ZrO2 may be 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0.

[0047] CeO2 is a photosensitizer that provides electrons for components such as Ag, Sb, and Sn. When the CeO2 content is lower than 0.01%, it cannot provide enough electrons, resulting in too low a crystal content of the photosensitive glass-ceramic, reducing the transmittance of the blackened part of the photosensitive glass-ceramic and the photosensitive glass-ceramic products, and reducing the Young's modulus of the photosensitive glass-ceramic and the photosensitive glass-ceramic products; when the CeO2 content is higher than 0.6%, the transmittance of the photosensitive glass-ceramic and the photosensitive glass-ceramic products in the transparent part is reduced, and the penetration depth of the photosensitive glass-ceramic and the photosensitive glass-ceramic products in the ultraviolet band is reduced, the crystal content inside the blackened part of the photosensitive glass-ceramic and the photosensitive glass-ceramic products is reduced, and the transmittance is increased. Therefore, the CeO2 content is 0.01-0.6%, preferably 0.07-0.4%, and more preferably 0.08-0.3%. In some embodiments, the present invention may include about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, .3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6% CeO2.

[0048] Ag2O, as a crystal nucleating agent for the photosensitive glass-ceramics and photosensitive glass-ceramics products of the present invention, plays a role in improving the blackening effect in the photosensitive glass-ceramics and photosensitive glass-ceramics products. When the content of Ag2O is less than 0.01%, the transmittance of the blackened part of the photosensitive glass-ceramics and photosensitive glass-ceramics products increases, and even cannot be blackened, and the drop ball test height of the photosensitive glass-ceramics and photosensitive glass-ceramics products decreases, the expansion coefficient increases, and the graphic accuracy decreases. When the content of Ag2O exceeds 0.8%, the transmittance of the transparent part of the glass decreases during the molding or heat treatment process, and due to the excessively high crystal nucleus content, the number of crystals in the photosensitive glass-ceramics and photosensitive glass-ceramics products increases, resulting in excessively fine grain size, and the scattering effect of the crystals in the blackened part on visible light is weakened, which easily leads to an increase in the transmittance of the blackened part, and the glass is easy to crystallize during molding. Therefore, the content of Ag2O is limited to 0.01-0.8%, preferably 0.1-0.6%, and more preferably 0.2-0.5%. In some embodiments, the present invention may include about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0. .4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.8% Ag2O.

[0049] The inventors have found that in some embodiments, the ratio of the content of Ag2O to the content of CeO2, Ag2O / CeO2, is controlled within the range of 1.0 to 10.0, and the grain size of the blackened portion of the photosensitive glass-ceramics and photosensitive glass-ceramics products is larger, the crystal content is higher, the light scattering effect in the visible light band is stronger, the transmittance of the blackened portion is lower, and the hardness and drop ball test height of the photosensitive glass-ceramics and photosensitive glass-ceramics products are increased. Therefore, preferably Ag2O / CeO2 is 1.0 to 10.0, more preferably Ag2O / CeO2 is 1.5 to 6.5, and further preferably Ag2O / CeO2 is 2.0 to 4.5. In some embodiments, the value of Ag2O / CeO2 can be 1.0, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0050] In some embodiments, the ratio of ZrO2 content to the total content of Ag2O and CeO2 Ag2O+CeO2 (ZrO2 / (Ag2O+CeO2)) is controlled within the range of 2.3 to 50.0, which can optimize the expansion coefficient of the glass and improve the accuracy of pattern formation in the photosensitive microcrystalline glass after mask exposure and heat treatment. At the same time, the transmittance of the transparent part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products is higher, and the transmittance of the blackened part is lower, and the hardness and ball drop height of the glass and photosensitive microcrystalline glass products can be improved. Therefore, ZrO2 / (Ag2O+CeO2) is preferably 2.3 to 50.0, more preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, further preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0. In some embodiments, the value of ZrO2 / (Ag2O+CeO2) may be 2.3, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19. 0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0.

[0051] During UV exposure, Sb2O3 and SnO2 absorb Ce 3+ The released electrons play the role of storing electrons and provide Ag for subsequent heat treatment. +Provide electrons to form Ag colloid nucleation and promote the blackening of photosensitive microcrystalline glass. When the content of Sb2O3+SnO2 is lower than 0.05%, it is difficult for photosensitive microcrystalline glass or photosensitive microcrystalline glass products to achieve the blackening effect. When the content of Sb2O3+SnO2 is higher than 1.2%, the blackened part of the photosensitive microcrystalline glass or photosensitive microcrystalline glass products tends to increase in transmittance. Therefore, the content of Sb2O3+SnO2 is 0.05-1.2%, preferably 0.1-1%, and more preferably 0.2-0.7%. In some embodiments, the content of Sb2O3+SnO2 is about 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, 1.2%.

[0052] SnO2 has a good effect of promoting the blackening of photosensitive microcrystalline glass, but in some embodiments, when the content of SnO2 is higher than 0.5%, the transmittance of the transparent part of the glass decreases or even devitrifies during molding or heat treatment. Therefore, the content of SnO2 is limited to 0-0.5%, preferably 0-0.3%, and more preferably 0-0.2%. The content of Sb2O3 is limited to 0-1%, preferably 0.01-0.7%, and more preferably 0.07-0.5%. In some embodiments, the present invention may comprise about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 4%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5% SnO2. In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% Sb2O3.

[0053] The inventors have found through a large number of experimental studies that in some embodiments, by controlling the ratio of the total content of Sb2O3 and SnO2 (Sb2O3+SnO2) / Ag2O between the content of Ag2O and the total content of Sb2O3 and SnO2 (Sb2O3+SnO2) / Ag2O within the range of 0.1 to 5.0, the dielectric loss of the glass can be reduced, the height of the falling ball test of the glass and the photosensitive microcrystalline glass products can be increased, the transparent part of the photosensitive microcrystalline glass and the photosensitive microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, preferably (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, more preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and further preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6. In some embodiments, the value of (Sb2O3+SnO2) / Ag2O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0054] In some embodiments, by controlling the ratio of the total content of Ag2O, SnO2 and Sb2O3 Ag2O+SnO2+Sb2O3 to the content of CeO2 (Ag2O+SnO2+Sb2O3) / CeO2 within the range of 1.0 to 30.0, the transmittance of the blackened part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products can be lowered, while reducing the dielectric constant of the glass and improving the hardness and Young's modulus. Therefore, the preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0~30.0, the more preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0~20.0, the further preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0~12.5, and the further preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5~10.0. In some embodiments, the value of (Ag2O+SnO2+Sb2O3) / CeO2 may be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5 , 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.

[0055] In some embodiments, controlling the ratio of the total content of Sb2O3, SnO2, and CeO2 (Sb2O3+SnO2+CeO2) to the content of Ag2O (Sb2O3+SnO2+CeO2) / Ag2O in the range of 0.1 to 10.0 can reduce the dielectric loss and expansion coefficient of the glass and make the transmittance of the blackened part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products lower. Therefore, the preferred (Sb2O3+SnO2+CeO2) / Ag2O is 0.1~10.0, the more preferred (Sb2O3+SnO2+CeO2) / Ag2O is 0.4~5.0, the further preferred (Sb2O3+SnO2+CeO2) / Ag2O is 0.7~3.7, and the further preferred (Sb2O3+SnO2+CeO2) / Ag2O is 1.5~3.2. In some embodiments, the value of (Sb2O3+SnO2+CeO2) / Ag2O may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4 , 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0056] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3) can adjust the dielectric constant and dielectric loss of the glass, and can be Ag +Provide electrons to promote the blackening of photosensitive microcrystalline glass. When Ln2O3 is higher than 5%, the transmittance of the blackened part of the photosensitive microcrystalline glass and photosensitive microcrystalline glass products increases, and the dielectric constant and dielectric loss of the glass increase. Therefore, the content of Ln2O3 is limited to 0-5%, preferably 0-3%, more preferably 0-1%. In some embodiments, it is further preferred that Ln2O3 is not contained. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% Ln2O3.

[0057] Fe2O3 can absorb ultraviolet light during the ultraviolet exposure of glass and can be used as Ag +Provide electrons to promote the blackening of photosensitive microcrystalline glass. When the content of Fe2O3 is higher than 1%, the transmittance of the transparent part of the photosensitive microcrystalline glass and the photosensitive microcrystalline glass products in the visible light band is reduced, the transmittance of the blackened part is increased, and the drop ball test height of the photosensitive microcrystalline glass and the photosensitive microcrystalline glass products is reduced. Therefore, the content of Fe2O3 is limited to 0-1%, preferably 0-0.5%, more preferably 0-0.2%. In some embodiments, it is further preferred that Fe2O3 is not contained. In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% Fe2O3.

[0058] The "does not contain" and "0%" recorded in this article means that the compound, molecule or element is not intentionally added as a raw material to the photosensitive glass, photosensitive glass-ceramic or photosensitive glass-ceramic product of the present invention; however, as raw materials and / or equipment for producing photosensitive glass, photosensitive glass-ceramic or photosensitive glass-ceramic products, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final photosensitive glass, photosensitive glass-ceramic or photosensitive glass-ceramic products. This situation is also within the scope of protection of the patent of this invention.

[0059] The performance indicators of the photosensitive glass-ceramics and / or photosensitive glass-ceramics products and / or photosensitive glass of the present invention are tested by the following methods:

[0060] <Light transmittance>

[0061] The light transmittance is tested according to the following method: the sample to be tested is processed into a certain thickness and the opposite surfaces are polished in parallel, and the test is carried out in accordance with the national standard "GB / T 7962.12-2010".

[0062] <Linear expansion coefficient>

[0063] Linear expansion coefficient (α20℃-300℃ ) The data of 20°C-300°C are tested according to the national standard "GB / T7962.16-2010". In the present invention, the linear expansion coefficient is sometimes referred to as the expansion coefficient.

[0064] <Dielectric constant>

[0065] Dielectric constant (ε r ) The test was conducted in accordance with the national standard GB / T 7265.1-1987, and the data was tested at 1GHz.

[0066] <Dielectric loss>

[0067] The dielectric loss (tanδ) is tested according to the national standard GB / T 7265.1-1987, and the data is tested under 1GHz conditions.

[0068] <Drop ball test height>

[0069] A φ20×1mm sample is placed on a glass supporting fixture, and a 32g steel ball is dropped from a specified height. The maximum drop ball test height at which the sample can withstand the impact without breaking is the drop ball test height. Specifically, the test is implemented starting from a drop ball test height of 100mm. Without breaking, the height is changed in sequence through 100mm, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm, 900mm, 100mm, 1000mm, 1100mm, 1200mm and above. For the embodiment with "drop ball test height II", photosensitive microcrystalline glass products are used as test objects. The test data recorded as 1000mm in the embodiment indicates that even if a steel ball is dropped from a height of 1000mm, the photosensitive microcrystalline glass products will withstand the impact without breaking. For the embodiment with "drop ball test height I", photosensitive glass is used as the test object. The drop ball test height in the present invention is sometimes referred to as the drop ball height.

[0070] <Knoop hardness>

[0071] The load (N) when a diamond quadrangular pyramid indenter with an angle of 172.5° is pressed into a pyramid-shaped depression on the test surface is divided by the surface area (mm2) calculated by the length of the depression. 2 ) value. The test load was 100 (N) and the holding time was 15 (seconds). In the present invention, Knoop hardness may be simply referred to as hardness.

[0072] <Young's modulus>

[0073] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.

[0074]

[0075] G=V S 2 ρ

[0076] Where: E is Young's modulus, Pa;

[0077] G is the shear modulus, Pa;

[0078] V T is the shear wave velocity, m / s;

[0079] V S is the longitudinal wave velocity, m / s;

[0080] ρ is the glass density, g / cm 3 .

[0081] <Refractive Index>

[0082] Refractive index (n d ) Tested according to the method specified in GB / T7962.1-2010.

[0083] The photosensitive glass of the present invention has the following properties:

[0084] 1) In some embodiments, the refractive index (n d ) is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284.

[0085] 2) In some embodiments, the Young's modulus (E) of the photosensitive glass of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa.

[0086] 3) In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm2 .

[0087] 4) In some embodiments, the drop ball test height I of the photosensitive glass of the present invention is greater than 200 mm, preferably greater than 300 mm, and more preferably greater than 400 mm.

[0088] 5) In some embodiments, the dielectric loss (tan δ) of the photosensitive glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 .

[0089] 6) In some embodiments, the dielectric constant (ε r ) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0.

[0090] 7) In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0091] The photosensitive glass-ceramics of the present invention has the following properties:

[0092] 1) In some embodiments, the average transmittance (T 400-800nm ) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0093] 2) In some embodiments, the average transmittance (T 400-800nm ) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0094] 3) In some embodiments, the transmittance (T 870nm ) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0095] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0096] In some embodiments, since the transparent portion of the photosensitive glass-ceramics of the present invention does not produce crystals, it has the same properties as the above-mentioned photosensitive glass, such as Young's modulus (E), Knoop hardness (Hk 0.1 ), drop ball test height, dielectric loss (tanδ), dielectric constant (ε r ), linear expansion coefficient (α 20℃-300℃ ) etc. Specifically, in some embodiments, the Young's modulus (E) of the transparent part of the photosensitive glass-ceramics of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 In some embodiments, the drop ball test height of the transparent part of the photosensitive microcrystalline glass of the present invention is 200 mm or more, preferably 300 mm or more, and more preferably 400 mm or more. In some embodiments, the dielectric loss (tan δ) of the transparent part of the photosensitive microcrystalline glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 In some embodiments, the dielectric constant (ε r ) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0. In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0097] The photosensitive glass-ceramic product of the present invention has the following properties:

[0098] 1) In some embodiments, the average transmittance (T 400-800nm) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0099] 2) In some embodiments, the average transmittance (T 400-800nm ) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0100] 3) In some embodiments, the transmittance (T 870nm ) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0101] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0102] 5) In some embodiments, the drop ball test height II of the photosensitive microcrystalline glass product of the present invention is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.

[0103] In some embodiments, the photosensitive glass / photosensitive glass-ceramics / photosensitive glass-ceramics products of the present invention have lower dielectric constants and dielectric losses, which can reduce transmission losses of electrical signals.

[0104] In some embodiments, the photosensitive glass / photosensitive glass-ceramics / photosensitive glass-ceramics products of the present invention have higher Knoop hardness, Young's modulus and ball drop height.

[0105] In some embodiments, the photosensitive glass / photosensitive glass-ceramics / photosensitive glass-ceramics products of the present invention have a lower linear expansion coefficient to improve the accuracy of optical signal channels or mask patterns.

[0106] In some embodiments, the photosensitive glass / photosensitive glass-ceramics / photosensitive glass-ceramics products of the present invention have a lower refractive index, which can reduce the reflectivity of surface light signals and increase the incidence rate of light signals.

[0107] The photosensitive glass-ceramics, photosensitive glass-ceramics products, and photosensitive glass of the present invention can be widely made into glass cover plates or glass components due to the above-mentioned excellent properties; at the same time, the photosensitive glass-ceramics, photosensitive glass-ceramics products, photosensitive glass of the present invention, and glass cover plates or glass components made thereof can be used to manufacture various instruments or equipment, including but not limited to electronic equipment, medical equipment, decorations or handicrafts, such as mobile phones, watches, computers, biomedical testing, etc., for manufacturing local light shielding glass or patterned cover glass for mobile phones, smart phones, tablet computers, laptops, televisions, etc., or optical signal channel glass for smart watches, biomedical devices, etc., or for manufacturing patterned decorations or handicraft glass.

[0108] The photosensitive glass, photosensitive glass-ceramics and photosensitive glass-ceramics products of the present invention can be produced and manufactured by the following method:

[0109] The manufacturing method of photosensitive glass comprises the following steps: weighing raw materials according to the component ratio and mixing them uniformly, placing the uniformly mixed raw materials into a platinum or quartz crucible, melting, clarifying, homogenizing and then cooling at 1450-1600°C, pouring the molten glass liquid into a mold for forming, and introducing circulating cooling air to ensure that the glass does not crystallize, preferably preheating the mold to 200-500°C, placing the formed glass and the mold into an annealing furnace for heat preservation and annealing, and then turning off the power and cooling with the furnace to obtain the photosensitive glass.

[0110] The manufacturing method of the photosensitive microcrystalline glass comprises the following steps: forming the photosensitive glass, subjecting the photosensitive glass to a crystallization process, or processing the photosensitive glass into a glass element of a specific shape and then subjecting the photosensitive glass to a crystallization process, to obtain the photosensitive microcrystalline glass of the present invention. The method of processing the glass element into a specific shape of the present invention includes methods known to those skilled in the art such as hot pressing, grinding or polishing. The crystallization process of the present invention comprises subjecting the photosensitive glass to a mask exposure process, and then subjecting the photosensitive glass to a crystallization heat treatment, and uniformly precipitating crystals at the glass exposure position. The mask exposure process of the present invention refers to ultraviolet exposure at a specific position or region of the photosensitive glass, and the wavelength of the ultraviolet light is preferably 280 to 360 nm, more preferably 300 to 330 nm, and further preferably 313 nm. A special photomask pattern can be customized according to the application requirements, and the exposure time is preferably 5 to 60 minutes. The crystallization heat treatment of the present invention can be carried out in one stage or in two stages, and preferably in two stages. The two-stage crystallization heat treatment refers to performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

[0111] The method for manufacturing the photosensitive glass-ceramic product comprises the following steps: subjecting the photosensitive glass-ceramic of the present invention to a chemical strengthening process, or processing the photosensitive glass-ceramic into a photosensitive glass-ceramic element of a specific shape and then subjecting the photosensitive glass-ceramic to a chemical strengthening process, to obtain the photosensitive glass-ceramic product of the present invention. The method of processing into a specific shape of the present invention comprises a method known to those skilled in the art such as hot pressing, grinding or polishing.

[0112] The chemical strengthening described in the present invention is an ion exchange method. During the ion exchange process, the smaller metal ions in the photosensitive glass-ceramics are replaced or "exchanged" by larger metal ions with the same valence near the photosensitive glass-ceramics. The larger ions replace the smaller ions, and compressive stress is built in the photosensitive glass-ceramics to form a compressive stress layer.

[0113] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na + , K + , Rb + , Cs + Ion exchange is performed by immersing the photosensitive glass-ceramic in a salt bath of at least one molten salt containing larger metal ions, which are used to replace smaller metal ions in the photosensitive glass-ceramic. Alternatively, other monovalent metal ions such as Ag + 、Tl + , Cu +The one or more ion exchange processes used to chemically strengthen the photosensitive glass-ceramic may include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions, with washing and / or annealing steps added between immersions.

[0114] In some embodiments, the photosensitive glass-ceramics can be ion exchanged by immersing in a salt bath of molten Na salt (such as NaNO3), and / or K salt (such as KNO3), and / or a mixed salt of Na and K at a temperature of about 350°C to 470°C for 1 to 36 hours, preferably in the temperature range of 380°C to 460°C, and preferably in the time range of 2 to 24 hours.

[0115] In some embodiments, the photosensitive glass of the present invention can be processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed by the above-mentioned crystallization process to obtain a photosensitive microcrystalline glass product. In some embodiments, the photosensitive glass of the present invention can be processed into a glass element, and then the glass element is processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed by the above-mentioned crystallization process to obtain a photosensitive microcrystalline glass product.

[0116] Example

[0117] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The present invention embodiments have been tried to ensure the accuracy of the values ​​(such as quantity, etc.), but some errors and deviations must be taken into account. The composition itself is given in weight % based on the oxide and has been standardized to 100%.

[0118] <Photosensitive Glass Example>

[0119] This embodiment adopts the above-mentioned method for manufacturing photosensitive glass to obtain photosensitive glass having the composition shown in Tables 1 to 4. In addition, the characteristics of each photosensitive glass are measured by the testing method of the present invention, and the measurement results are shown in Tables 1 to 4.

[0120] Table 1.

[0121]

[0122]

[0123] Table 2.

[0124]

[0125]

[0126] Table 3.

[0127]

[0128]

[0129] Table 4.

[0130]

[0131]

[0132] <Photosensitive glass-ceramic embodiment>

[0133] This embodiment adopts the above-mentioned method for manufacturing photosensitive microcrystalline glass to obtain photosensitive microcrystalline glass having the composition shown in Table 5 to Table 8. In addition, the characteristics of each photosensitive microcrystalline glass are measured by the testing method described in the present invention, and the measurement results are shown in Table 5 to Table 8. The transmittance of the photosensitive microcrystalline glass in the following embodiments is tested using a 1 mm thick sample.

[0134] Table 5.

[0135]

[0136]

[0137] Table 6.

[0138]

[0139]

[0140] Table 7.

[0141]

[0142]

[0143] Table 8.

[0144]

[0145]

[0146] <Photosensitive glass-ceramic product example>

[0147] This embodiment adopts the manufacturing method of the above-mentioned photosensitive glass-ceramic products to obtain photosensitive glass-ceramic products having the compositions shown in Tables 9 to 12. In addition, the properties of each photosensitive glass-ceramic product are measured by the testing method described in the present invention, and the measurement results are shown in Tables 9 to 12. The transmittance of the photosensitive glass-ceramic products in the following embodiments is tested using a 1 mm thick sample.

[0148] Table 9.

[0149]

[0150]

[0151] Table 10.

[0152]

[0153]

[0154] Table 11.

[0155]

[0156]

[0157] Table 12.

[0158]

[0159]

Claims

1. A method for manufacturing photosensitive glass-ceramics, characterized in that: The method comprises the following steps: forming photosensitive glass, and subjecting the photosensitive glass to a crystallization process to form photosensitive microcrystalline glass, wherein the photosensitive microcrystalline glass comprises one or more blackened parts and one or more transparent parts, wherein the blackened parts contain a crystalline phase, and the transparent parts do not contain a crystalline phase.

2. The method for manufacturing photosensitive glass-ceramics according to claim 1, characterized in that: The crystallization process includes performing mask exposure treatment on the photosensitive glass and then performing crystallization heat treatment. The mask exposure treatment includes performing ultraviolet exposure on a specific position or area of ​​the photosensitive glass. The wavelength of the ultraviolet light is preferably 280 to 360 nm, more preferably 300 to 330 nm, and further preferably 313 nm. The exposure time is preferably 5 to 60 minutes.

3. The method for manufacturing photosensitive glass-ceramics according to claim 1, characterized in that: The crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes a nucleation process at a first temperature, and then a crystal growth process at a second temperature higher than the nucleation process temperature. The first temperature is preferably 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. The second temperature is preferably 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

4. The method for manufacturing photosensitive glass-ceramics according to claim 1, characterized in that: The photosensitive glass-ceramics contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase, more preferably, in the blackened portion of the photosensitive glass-ceramics, the weight percentage of the lithium metasilicate crystalline phase is 5 to 50%, further preferably, in the blackened portion of the photosensitive glass-ceramics, the weight percentage of the lithium metasilicate crystalline phase is 5 to 40%, and further preferably, in the blackened portion of the photosensitive glass-ceramics, the weight percentage of the lithium metasilicate crystalline phase is 10 to 30%.

5. The method for manufacturing photosensitive glass-ceramics according to claim 1, characterized in that: The average transmittance T of the transparent part of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm in the 400 to 800 nm band 400-800nm is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2-1.5 mm in the wavelength range of 400-800 nm is 400-800nm 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm at 870 nm 870nm is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the photosensitive microcrystalline glass with a thickness of 0.2 to 1.5 mm at 940 nm 940nm It is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.

6. The method for manufacturing photosensitive glass-ceramics according to claim 1, characterized in that: The components of the photosensitive microcrystalline glass are expressed by weight percentage and contain: SiO2: 65-78%, preferably SiO2: 68-77%, more preferably SiO2: 69.5-75.5%; and / or R2O+Li2O+Al2O3: 15-30%, preferably R2O+Li2O+Al2O3: 17.5-29.5%, more preferably R2O+Li2O+Al2O3: 18.5-26%, further preferably R2O+Li2O+Al2O3: 20-25%; and / or ZrO2: 1.5-10%, preferably ZrO2: 2-8%, more preferably ZrO2: 3-6.5%; and / or CeO2: 0.01-0.6%, preferably CeO2: 0.07-0.4%, more preferably CeO2: 0.08-0.3%; and / or Ag2 O: 0.01~0.8%, preferably Ag2O: 0.1~0.6%, more preferably Ag2O: 0.2~0.5%; and / or Sb2O3+SnO2: 0.05~1.2%, preferably Sb2O3+SnO2: 0.1~1%, more preferably Sb2O3+SnO2: 0.2~0.7%; and / or Ln2O3: 0~5%, preferably Ln2O3: 0~3%, more preferably Ln2O3: 0~1%, further preferably does not contain Ln2O3; and / or Fe2O3: 0~1%, preferably Fe2O3: 0~0.5%, more preferably Fe2O3: 0~0.2%, further preferably does not contain Fe2O3, the R2O is one or two of Na2O, K2O, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

7. The method for manufacturing photosensitive glass-ceramics according to any one of claims 1 to 6, characterized in that: The components of the photosensitive microcrystalline glass are expressed in weight percentage, wherein: SiO2 / Li2O is 5.5-10.0, preferably SiO2 / Li2O is 6.0-9.0, and more preferably SiO2 / Li2O is 7.0-8.5; and / or (K2O+Na2O) / ZrO2 is 0.5-7.1, preferably (K2O+Na2O) / ZrO2 is 0.7-4.5, and more preferably (K2O+Na2O) / ZrO2 is 0.8-2.5; and / or Li2O / ZrO2 is 1.0-7.5, preferably Li2O / ZrO2 is 1.2-5.0, and more preferably Li2O / ZrO2 is 1.4-4.3, and further preferably Li2O / ZrO2 is 1.6-3.0; and / or (SiO2+Li2O) / Zr rO2 is 8.0~55.0, preferably (SiO2+Li2O) / ZrO2 is 10.0~37.0, more preferably (SiO2+Li2O) / ZrO2 is 12.0~25.0, and further preferably (SiO2+Li2O) / ZrO2 is 13.0~20.0; and / or (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0~7.5, preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7~6.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3~6.0, and further preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8~5.

8.

8. The method for manufacturing photosensitive glass-ceramics according to any one of claims 1 to 6, characterized in that: The components of the photosensitive microcrystalline glass are expressed in weight percentage, wherein: (Sb2O3+SnO2) / Ag2O is 0.1-5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5-3.5, more preferably (Sb2O3+SnO2) / Ag2O is 1.0-2.6; and / or Ag2O / CeO2 is 1.0-10.0, preferably Ag2O / CeO2 is 1 .5~6.5, more preferably Ag2O / CeO2 is 2.0~4.5; and / or ZrO2 / (Ag2O+CeO2) is 2.3~50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5~35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5~20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0~1 8.0; and / or (Ag2O + SnO2 + Sb2O3) / CeO2 is 1.0 to 30.0, preferably (Ag2O + SnO2 + Sb2O3) / CeO2 is 3.0 to 20.0, more preferably (Ag2O + SnO2 + Sb2O3) / CeO2 is 5.0 to 12.5, and further preferably (Ag2O + SnO2 + Sb2O3) / CeO2 is 7.5 to 1 0.0; and / or (Sb2O3+SnO2+CeO2) / Ag2O is 0.1~10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4~5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7~3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5~3.

2.

9. The method for manufacturing photosensitive glass-ceramics according to any one of claims 1 to 6, characterized in that: The components of the photosensitive microcrystalline glass are expressed in weight percentage, wherein: R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; and / or Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; and / or Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; and / or Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; and / or SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%, wherein R2O is one or both of Na2O and K2O.

10. The method for manufacturing photosensitive glass-ceramics according to any one of claims 1 to 6, characterized in that: The refractive index n of the transparent part of the photosensitive microcrystalline glass d is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284; and / or Young's modulus E is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 ; and / or the ball drop test height I is 200 mm or more, preferably 300 mm or more, more preferably 400 mm or more; and / or the dielectric loss tanδ is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 ; and / or dielectric constant ε r 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0; and / or linear expansion coefficient α 20℃-300℃ 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

11. Photosensitive glass-ceramics, characterized in that: The photosensitive microcrystalline glass is manufactured by the manufacturing method of any one of claims 1 to 10.

12. A photosensitive glass-ceramic product, characterized in that: The photosensitive microcrystalline glass according to claim 11 is made through a chemical strengthening process.

13. The photosensitive glass-ceramic product according to claim 12, characterized in that: The chemical strengthening process includes immersing the photosensitive microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.

14. The photosensitive glass-ceramic product according to claim 12 or 13, characterized in that: The drop ball test height II of the photosensitive microcrystalline glass product is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.

15. A glass cover plate, characterized in that: A photosensitive glass-ceramic product comprising the photosensitive glass-ceramic product according to claim 11, or any one of claims 12 to 14.

16. A glass component, characterized in that: A photosensitive glass-ceramic product comprising the photosensitive glass-ceramic product according to claim 11, or any one of claims 12 to 14.

17. A device, characterized in that Containing the photosensitive microcrystalline glass according to claim 11, and / or containing the photosensitive microcrystalline glass product according to any one of claims 12 to 14, and / or containing the glass cover plate according to claim 15, and / or containing the glass component according to claim 16.